Sub acromial debridement surgery with acromioplasty for chronic shoulder pain - biomechanical challenges in physical rehabilitation - Leonard JH,; Siti Salmiah MD,; Das S,; Vikram M,; Ayiesah HR, (Department of Surgery, UKM Medical Centre, 2011)
Arthroscopic sub acromial debridement surgery with acromioplasty is one of the shoulder surgeries performed to treat chronic shoulder pain. This surgical procedure is usually indicated in sub acromial impingement syndrome of shoulder, degenerative rotator cuff tears, severe functional limitation of shoulder joint and often surgery was performed in cases where all the conservative management had failed in the treatment of chronic shoulder pain. Even though the patient would be referred for early rehabilitation, post operative management of this surgical condition is highly challenging. Movement of the shoulder joint is often related with scapulo-thoracic joint, acromio-clavicular joint and sternoclavicular joint and the shoulder movements are governed by various different muscular forces from these joints. Failure to understand this biomechanical complexity of shoulder joint during post operative rehabilitation results in failure of the surgical outcome and might cause severe functional limitation with recurrent shoulder pain. Often in clinical practice, greater emphasis is given to achieve and regain movements in shoulder joint at the expense of the joint stability. However, inadequate scapular stability might further predispose the shoulder joint to excessive loading and results in repetitive injuries leading to chronic shoulder pain. This might affect the surgical and clinical outcome of the acromioplasty and result in surgical failure. Hence, surgeons and clinicians need to understand the biomechanical contributions in the post operative rehabilitation of the shoulder joint. The present case report emphasises the biomechanical model of post operative rehabilitation of a patient who had arthroscopic sub acromial debridement with acromioplasty.